2018
DOI: 10.3389/fmed.2018.00335
|View full text |Cite
|
Sign up to set email alerts
|

From Vascular Smooth Muscle Cells to Folliculogenesis: What About Vasorin?

Abstract: First described in 1988, vasorin (VASN) is a transmembrane glycoprotein expressed during early mouse development, and with a less extent, in various organs and tissues (e.g., kidney, aorta, and brain) postnatally. Vasn KO mice die after 3 weeks of life from unknown cause(s). No human disease has been associated with variants of this gene so far, but VASN seems to be a potential biomarker for nephropathies and tumorigenesis. Its interactions with the TGF-β and Notch1 pathways offer the most serious assumptions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 23 publications
1
35
0
Order By: Relevance
“… 36 VASN deficiency causes unknown death within 3 weeks. 7 Our data corresponded with those in previous studies showing sudden death in young VASN −/− mice (Figure 2 ). Our unpublished studies also showed that VASN deficiency induces inflammation and pathology in the lung, kidney and liver.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“… 36 VASN deficiency causes unknown death within 3 weeks. 7 Our data corresponded with those in previous studies showing sudden death in young VASN −/− mice (Figure 2 ). Our unpublished studies also showed that VASN deficiency induces inflammation and pathology in the lung, kidney and liver.…”
Section: Discussionsupporting
confidence: 93%
“… 6 Soluble VASN protein can bind to TGF‐β, which can inhibit epithelial‐to‐mesenchymal transition. 7 A previous study showed high VASN expression in human glioblastoma in the context of TNF α‐induced apoptosis. 7 CRISPR/Cas9 technology could be used to generate a knockout mouse model to further study the function of VASN and its associated signalling pathway.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…For instance, vasorin (VASN) was found to modulate arterial response to injury in vivo [ 38 ]. It also appears to be involved in cellular migration and proliferation/differentiation [ 39 ]. Neural cell adhesion molecule-1 (NCAM1) is involved in cell–cell and matrix adhesion in cardiomyocytes adhesion [ 40 ], and is upregulated under metabolic stress [ 41 ].…”
Section: Discussionmentioning
confidence: 99%